2021
DOI: 10.1002/vetr.15
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with food‐animal producer visit‐specific satisfaction following on‐farm interaction with a veterinarian

Abstract: Background: Effective communication has been found to have positive associations with client satisfaction, client adherence and veterinarian satisfaction in companion animal medicine. Better understanding the role of communication on these outcomes, specifically producer satisfaction, is likely to benefit food‐animal medicine. Objectives were to identify factors associated with producer visit‐specific satisfaction following on‐farm veterinarian–producer interactions and evaluate the validity of the Client Sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The VPPC compromises nine items and uses a four-point response format ( [1] not at all, [2] a little, [3] mostly, [4] completely). Reliability of the VPPC based on the current study population has been previously reported (Cronbach's alpha = 0.74) 9 and was considered acceptable. 14 A third veterinarian survey was administered after each data collection day.…”
Section: Data Collectionmentioning
confidence: 70%
See 4 more Smart Citations
“…The VPPC compromises nine items and uses a four-point response format ( [1] not at all, [2] a little, [3] mostly, [4] completely). Reliability of the VPPC based on the current study population has been previously reported (Cronbach's alpha = 0.74) 9 and was considered acceptable. 14 A third veterinarian survey was administered after each data collection day.…”
Section: Data Collectionmentioning
confidence: 70%
“…Data collection has been previously described 9 . In brief, eligible food‐animal veterinarians in Ontario were enlisted to the study, using one of two different recruitment methods, a convenience sample (2018 and 2019) and a simple random sample (2019 only).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations